Analyses of Individual and Organizational Competences Associated with Knowledge Management Practice - de Sordi, José Osvaldo; Azevedo, Marcia Carvalho (Review of Business Management, 2008)
The research analyzed critical aspects of the knowledge management process, based on the analyses of knowledge, abilities and attitudes required to individual knowledge workers and to organizations responsible for the management process. In the present work a characterization of the knowledge management process was developed and information and knowledge workers were defined. Competence concept was discussed and specialists gave opinions about critical competences to knowledge management process. The opinions were organized and analyzed by the Delphi method. The results aggregate value to the management context by discussing an extremely important resource to organizations – knowledge – and because they support its management process. The research identified wide critical aspects that are compatible with current organizational challenges, directing the process management to important themes as: the worker able to create, the organization able to convert individual knowledge into organizational knowledge, knowledge sharing while still tacit, the maximization of organizational knowledge use, information and knowledge generation and preservation, among others important topics to be observed by knowledge workers and by administrators responsible for the knowledge management process. Key-words: Competence. Knowledge management. Knowledge worker. Individual and organizational competence.